PENGARUH MEDIA POP-UP BOOK TERHADAP MINAT DAN HASIL BELAJAR PADA SISTEM PENCERNAAN MANUSIA KELAS VIII SISWA SMP NEGERI 1 LAMASI - sohriati, eva; Nursyamsiah; Nurasia; Mutmainna Ekawati (Universitas Cokroaminoto Palopo, 2024)
The aim of this research was to determine the effect of Pop-Up Book media on interest and learning outcomes on the human digestive system of class VIII students. This type of research is the type of research used in this research is quantitative, namely collecting, compiling, managing and analyzing data in the form of numbers. The research design used is Quasi Experimental Design. The research design used in the form of a quasi experiment is Nonequivalent Control Group Design. This design is similar to the pretest-posttest Control Group Design. The sample for this research was class VIII students at SMP Negeri 1 Lamasi with a total of 30 students. The results of the research and discussion show that the significant value of Sig. (2-tailed) is 0.000 < 0.05. then H0 is rejected. and H1 is accepted. There is an influence in the use of Pop-Up Book media on human digestive system material on the learning outcomes of class VIII.B students at SMP Negeri 1 Lamasi.